A uranium(IV) imido amido triazenido complex formed via addition of a CH bond across a UN multiple bond. (15th November 2018) - Boreen, Michael A.; Arnold, John
Graphical abstract: A uranium(IV) imido amido triazenido complex was synthesized using a bulky m -terphenyl azide. The formation of the molecule involves CH bond addition across a uranium–imido bond and insertion of aryl azide into the resulting UC bond. X-ray crystallography and 1 H spectroscopy show a highly asymmetric solid- and solution-state structure. Abstract: Addition of three equivalents of KC8 to a mixture of UI3 (1, 4-dioxane)1.5 and three equivalents of a bulky m -terphenyl azide led to the isolation of a uranium(IV) complex containing an imido, an amido, and a triazenido group on the same metal center. The amido moiety was formed via addition of an aryl CH bond across a UNimido bond, and an equivalent of the terphenyl azide inserted into the resulting UC bond. X-ray crystallography revealed a highly asymmetric solid-state structure, and 1 H NMR spectroscopy confirmed low solution-state symmetry. This work demonstrates alternate reaction pathways that must be considered when attempting to prepare uranium complexes with multiple imido groups.